Evaluasi Kinerja Aparatur Sipil Negara Dalam Menunjang Administrasi dan Kepegawaian Pada Sub Bagian Umum dan Kepegawaian Pemerintah Kecamatan Kayan Hilir, Kabupaten Sintang - Kariana Noviana; Netty Herawati; A. Arifin (Universitas Warmadewa, 2026)
This study aims to analyze the performance evaluation of Civil Servants (ASN) in supporting administrative and personnel functions at the General and Personnel Subdivision of Kayan Hilir Subdistrict Office, Sintang Regency. The research problem lies in the suboptimal understanding of administrative regulations and the lack of promptness and independence in performing administrative tasks. This study employs a descriptive method with a qualitative approach, utilizing in-depth interviews, observation, and documentation as data collection techniques. The findings indicate that, based on Levine’s framework as cited in Dwiyanto (2016), ASN performance has not been optimal across three key dimensions. In terms of accountability, inconsistencies in task implementation and reporting reflect weak performance accountability. Regarding responsibility, although tasks are carried out in accordance with formal duties, effectiveness is constrained by uneven understanding of procedures, high workload, and limited number of personnel. In terms of responsiveness, the ability of ASN to respond to administrative needs remains insufficiently adaptive, as indicated by delays in service delivery, inaccuracies in task completion, and dependence on document completeness and internal coordination. Overall, the evaluation reveals a gap between normative performance standards and empirical practices, indicating that ASN performance remains at a formal-procedural level and has not yet achieved substantive performance. This study recommends strengthening supervision, enhancing personnel capacity, improving coordination, and managing workload more systematically to achieve more effective, consistent, and accountable performance